The role of teachers' disciplinary semiotic knowledge in supporting young bi/multilingual learners' academic and reflexive multiliteracies. (22nd December 2020) - Humphrey, Sally
Abstract: This paper reports on research which has explored essential requirements for pedagogies of hope, including the expansion of teachers' semiotic knowledge. The study, a professional learning intervention with teachers of young multilingual learners engaged in science inquiry, was informed by Systemic Functional Linguistics (SFL) descriptions of verbal language and image in scientific representations. SFL's metalanguage provided resources for teachers to support their learners' academic and reflexive literacies in a number of ways. With academic mentors, the teachers used SFL's analytical tools to reveal learners' existing literacy repertoires in relation to the demands of curriculum tasks and to design lesson sequences to infuse support for multiliteracies within science content learning. Analysis of the multimodal texts composed by students provides evidence of the positive impact of culturally sustaining SFL on bi/multilingual learners' writing, including learners who had previously been challenged to demonstrate their science learning in writing and those who had achieved curriculum expectations. Significantly, teachers' developing semiotic knowledge allowed them to engage all students in substantive and reflexive conversations of scientific communication.